Stimulation of transient versus sustained ERK1/2 phosphorylation by relative chitinase-like proteins CHI3L1 and CHI3L2 correlates with different kinase localization and biological outcome - Areshkov, P.O.; Avdieiev, S.S.; Iershov, A.V.; Kavsan, V.M. (Вiopolymers and Cell, 2011)
Aim. To determine 293 and U373 cell response and ERK1/2 activation profile after CHI3L1 or CHI3L2 treatment. Methods. Specific activation and localization of ERK1/2 kinases after CHI3L1 or CHI3L2 addition to unsupplemented cell medium were evaluated by Western blots, immunofluorescence and confocal microscopy. To
determine whether CHI3L1 or CHI3L2 can enhance mitogenesis, [3H]thymidine incorporation in cellular DNA
was measured. Results. The obtained results show that ERK1/2 phosphorylation was stimulated in both cell types (293 and U373 cells) following addition of CHI3L2 or CHI3L1 in dose- and time-dependent manner. Unexpectedly, in opposite to CHI3L1, the dose-dependent decreasing of measured mitogenesis parameters was observed in 293 and U373 cells. In both cell types the treatment with CHI3L2 gave more sustained than CHI3L1
MAPK-pathway activation with prolonged phospho-ERK1/2 nuclear accumulation in 293 cells. Conclusions. In
contrast to the activation of ERK1/2 phosphorylation by CHI3L1 cell treatment, that leads to a proliferative signal, the activation of these kinases by CHI3L2 addition inhibits cell mitogenesis and proliferation in serum starved 293 and U373 cells.
Keywords: chitinase 3-like 1 protein (CHI3L1), chitinase 3-like 2 protein (CHI3L2), MAP kinase, mitogenesis. Мета. Визначити клітинну відповідь та встановити профіль активації кіназ ERK1/2 після обробки клітин 293 та U373 білками
CHI3L1 чи CHI3L2. Методи. Специфічну активацію і локалізацію кіназ ERK1/2 після внесення білків CHI3L1 або CHI3L2 до клітинного середовища, що не містить сироватки, проаналізовано
Вестерн-блот аналізо та методами імунофлуоресценції і конфокальної мікроскопії. Для встановлення, чи зможе додавання білків
CHI3L1 або CHI3L2 посилювати мітогенез, застосовано аналіз
інкорпорації [3H]тимідину в клітинну ДНК. Результати. Отримані результати демонструють, що стимуляція фосфорилювання кіназ ERK1/2 після додавання CHI3L1 або CHI3L2 має дозо- та
часозалежний характер. Виявилося, що, на відміну від CHI3L1, дозозалежне пригнічення інкорпорації [3H]тимідину констатовано у 293 та U373 клітинах. В обох типах клітин обробка білком
CHI3L2 викликає тривалішу активацію каскаду МАРК, ніж обробка білком CHI3L1, з акумулюванням кіназ ERK1/2 у ядрі клітин
293. Висновки. На противагу активації фосфорилювання кіназ
ERK1/2 внаслідок обробки клітин білком CHI3L1, що спричиняє
проліферацію, стимуляція цих кіназ додаванням білка CHI3L2 пригнічує мітогенез у клітинах 293 та U373, що перебувають у стані
сироваткового голодування.
Ключові слова: хітиназа 3-подібний білок 1 (CHI3L1), хітиназа 3-подібний білок 2 (CHI3L2), MAP-кіназа, мітогенез. Цель. Определить клеточный ответ и профиль активации киназ
ERK1/2 после обработки клеток 293 и U373 белками CHI3L1 или
CHI3L2. Методы. Специфическую активацию и локализацию киназ ERK1/2 после внесения белков CHI3L1 или CHI3L2 в клеточную среду, где отсутствует сыворотка, проанализировано методами Вестерн-блот анализа, иммунофлуоресценции и конфокальной микроскопии. Для определения, будет ли добавление белков
CHI3L1 или CHI3L2 увеличивать митогенез, использован анализ
инкорпорации [3H]тимидина в клеточную ДНК. Результаты. Полученные результаты демонстрируют, что стимуляция фосфорилирования киназ ERK1/2 после добавления CHI3L1 либо CHI3L2
имеет зависящий от дозы и времени характер. Оказалось, что, в
отличие от CHI3L1, дозозависимое угнетение инкорпорации [3H]
тимидина констатировано в 293- и U373-клетках. В обоих типах
клеток обработка белком CHI3L2 вызывает более длительную
активацию каскада МАРК, нежели обработка белком CHI3L1, с
аккумуляцией киназ ERK1/2 в ядрах клеток 293. Выводы. В отличие от активации фосфорилирования киназ ERK1/2 после обработки клеток белком CHI3L1, приводящей к пролиферации, стимуляция этих киназ добавлением белка CHI3L2 угнетает митогенез в клетках 293 и U373, находящихся в состоянии сывороточного голодания.
Ключевые слова: хитиназа 3-подобный белок 1 (CHI3L1), хитиназа 3-подобный белок 2 (CHI3L2), MAP-киназа, митогенез.